Backyard World/Canadian Culture: Looking at Festival Agendas - Greenhill, Pauline (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
Festivals enact agendas that are at times hegemonic, and at other times resistant. The Winnipeg Folk Festival and Folklorama, though otherwise disparate, have common concerns with both ethnicity and music but their multiculturalisms are fundamentally, structurally different. Folklorama reduces difference to make it palatable to mainstream culture; diversity gives way to standardization and sameness. In contrast, the Winnipeg Folk Festival, within circumscribed limits, opens a space for divergent expression. Folklorama is accessible financially, spatially, and temporally to people with a range of incomes. The Winnipeg Folk Festival requires more time and financial resources of its audiences.